Analisis Perbandingan Kinerja Keuangan Pada PT Indo Kordsa Tbk dan PT Indomobil Sukses Internasional Tbk - Aprilia, Fitratul Eka; Puji Muniarty (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze and compare the financial performance of PT Indo Kordsa Tbk and PT Indomobil Sukses Internasional Tbk for the period 2017-2021. The analysis uses key financial ratios including liquidity ratios (Current Ratio and Quick Ratio), profitability ratios (Net Profit Margin, ROA, and ROE), and solvency ratios (Debt to Equity Ratio). The method used is a comparative descriptive method with secondary data obtained from the company's annual financial statements. The results show that PT Indo Kordsa Tbk has a much better and more stable liquidity performance compared to PT Indomobil Sukses Internasional Tbk. In terms of profitability, both companies experienced fluctuations, but PT Indo Kordsa Tbk tended to show better efficiency in generating profits compared to PT Indomobil Sukses Internasional Tbk which had thin margins. In terms of solvency, PT Indomobil Sukses Internasional Tbk has a significantly higher dependency on debt compared to PT Indo Kordsa Tbk which is more conservative in its capital structure.